Salivary and plasmatic levels of tumor necrosis factor‐alpha do not correlate with the clinicopathological profile in breast cancer patients. Issue 4 (13th October 2022) - Opolski, Marcelo Marcos; Maito, Vitor Teixeira; Kawassaki, Aedra Carla Bufalo; da Silva, Janaína Carla; Kern, Rodrigo; Rech, Daniel; de Oliveira, Stefania Tagliari; Lonardoni Micheletti, Pâmela; Panis, Carolina; Grassiolli, Sabrina
Abstract: Herein, we evaluated the salivary and plasmatic levels of tumor necrosis factor‐alpha (TNF‐α) in women diagnosed with breast cancer (BC; n  = 20) versus women with benign breast conditions (Control; n  = 29) and correlated the TNF‐α findings with BC clinicopathological parameters. TNF‐α was higher in the saliva samples from both groups than in plasma levels. BC and Control patients presented similar plasmatic and salivary values of TNF‐α. The salivary and plasmatic values of TNF‐α did not correlate with tumor features (estrogen receptor; progestogen receptor; Ki67, and HER2), indicating that its salivary content does not correlate with the parameters of disease prognosis. Therefore, TNF‐α is not helpful as a salivary marker in breast cancer patients. Abstract : Tumor necrosis factor (TNF) levels in saliva and plasma samples from patients diagnosed with breast cancer do not correlate with clinicopathological features that are indicative of disease prognosis.